2014
DOI: 10.1039/c4ta05257a
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific catalytic activity in exfoliated MoS2single-layer polytypes for hydrogen evolution: basal plane and edges

Abstract: We performed ab initio calculations on the basic set of MoS 2 single-layer materials, namely the 1H, 1T and 1T 0 polytypes, to lay a theoretical framework on the emerging breakthrough-discoveries of high activity towards the hydrogen evolution reaction (HER) in exfoliated MoS 2 and related materials. Our calculations show that for exfoliated MoS 2 , 1T 0 is the most HER active polytype, with active sites both on the basal plane and at the edges of the layered grains. In comparison, the basal planes of the 1H a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
157
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(178 citation statements)
references
References 43 publications
13
157
0
8
Order By: Relevance
“…1(b) and (c), which indicate that MoSe 2 monolayer is semiconductor with a direct band gap of 1.45 eV. Additional, the spinpolarization calculation shows 1H-MoSe 2 is nonmagnetic, which is similar with monolayer MoS 2 [33]. Further calculation was performed by adopting the hybrid functional (HSE06) [34,35] to predict accurate band gap.…”
Section: Resultsmentioning
confidence: 97%
“…1(b) and (c), which indicate that MoSe 2 monolayer is semiconductor with a direct band gap of 1.45 eV. Additional, the spinpolarization calculation shows 1H-MoSe 2 is nonmagnetic, which is similar with monolayer MoS 2 [33]. Further calculation was performed by adopting the hybrid functional (HSE06) [34,35] to predict accurate band gap.…”
Section: Resultsmentioning
confidence: 97%
“…47,48,50 The adsorbed H prefers to bind to the surface S atoms, regardless of the coverage. Our previous work showed that the metastable 1T MoS 2 can be stabilized by hydrogenation and after a crossover coverage of 25%, the 1T phase becomes more stable than the 2H phase.…”
Section: Gibbs Free Energy (∆G H ) Of Atomic Hydrogen On the Surface mentioning
confidence: 98%
“…In this mechanism, the MoS 2 surface serves as both an anode and a cathode; electrons are generated at one site through an anodic reaction and conduct to the second site where a cathodic reaction occurs with the surrounding medium (see eqn (1) and (2)). The rapid oxidation of the 1T/1T′ phase is hypothesized to be the direct result of its electrical conductivity, 3335 which allows the required internal electron transfer, while the insulating 1H phase does not. The driving force for the corrosion-type mechanisms can be calculated using the computational hydrogen electrode (CHE) technique 36,37 applied to these two initiation reactions: Anodic:0.2em+H2normalOOH+false(H++efalse) Cathodic:0.2em+O2+false(H++efalse)OOH where “*” denotes a site on the MoS 2 nanosheet.…”
mentioning
confidence: 99%